Targeting Pathways Associated with SUMOylation and Hypoxia in Head and Neck Cancer - Niva, Saana (My University, 2025)
Head and neck cancers (HNCs) are the seventh most common type of malignancies worldwide, predominantly classified histologically as head and neck squamous cell carcinomas (HNSCC). These cancers represent a diverse group of malignancies characterized by heterogeneous and complex biological features, making disease management challenging. Advanced HNSCC has high relapse rate and poor prognosis. SUMOylation is a post-translational modification process, involving small ubiquitin-like modifiers (SUMOs), that regulates protein stability, localization and activity. It has a pivotal role in the regulation of various cellular functions, such as DNA repair and responses to stress conditions like hypoxia. However, dysregulation of SUMOylation has been associated with multiple aspects of cancer progression and metastasis. Hypoxia, a condition of insufficient oxygen supply, is a common feature of solid cancers like HNSCCs. It contributes to malignant characteristics by activating genes involved in angiogenesis, metastasis, and cell survival, which correlate with poorer prognosis. The SUMOylation pathway has been suggested to regulate hypoxia-inducible factors (HIFs), the main regulators of cellular responses to hypoxia, whereas hypoxia itself has been shown to alter the SUMOylation. However, little is known of the potential crosstalk between these pathways in HNSCC. The essential role of SUMOylation in tumorigenesis has led to studies evaluating the SUMOylation cascade as a potential therapeutic target in cancer management. Preclinical evidence suggests that the inhibition of the SUMO pathway could represent a promising therapeutic approach in cancer. However, in IHNSCC the potential of targeting this pathway remains poorly understood. The primary goal of this MSc thesis is to investigate the crosstalk between SUMOylation and hypoxia-related pathways in HNSCC pathogenesis. Additionally, this study aims to assess the potential of SUMOylation inhibition as a therapeutic strategy for HNSCC.
Keywords: Head and Neck Cancer, Head and Neck Squamous Cell Carcinoma (HNSCC), SUMOylation, Hypoxia